2014
DOI: 10.1002/2013je004519
|View full text |Cite
|
Sign up to set email alerts
|

MSL-APXS titanium observation tray measurements: Laboratory experiments and results for the Rocknest fines at theCuriosityfield site in Gale Crater, Mars

Abstract: The Mars Science Laboratory (MSL) rover, Curiosity, has a titanium science observation tray (o-tray), upon which portions from drilled and scooped Martian samples can be delivered for analyses by the Alpha-Particle X-ray Spectrometer (APXS). The standard APXS calibration approach to derive elemental concentrations cannot be applied to samples on the o-tray because they (1) have a nonuniform three-dimensional distribution within the APXS field of view and (2) are thin (< 50 μm) compared to the APXS information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Navigation camera (Navcam) images [Maki et al, 2012] confirmed that these fines were subsequently cleaned off of the center of the o-tray by the vibration and movement of fines scooped from the Rocknest sand shadow and portioned to the o-tray for analysis (Sols 91-95) [Berger et al, 2014]. Upon landing on 6 August 2012, the MSL sky crane retrorockets lofted surface fines from a depth of several centimeters, and a thin layer settled onto the o-tray.…”
Section: Methodsmentioning
confidence: 94%
See 3 more Smart Citations
“…Navigation camera (Navcam) images [Maki et al, 2012] confirmed that these fines were subsequently cleaned off of the center of the o-tray by the vibration and movement of fines scooped from the Rocknest sand shadow and portioned to the o-tray for analysis (Sols 91-95) [Berger et al, 2014]. Upon landing on 6 August 2012, the MSL sky crane retrorockets lofted surface fines from a depth of several centimeters, and a thin layer settled onto the o-tray.…”
Section: Methodsmentioning
confidence: 94%
“…To do this, we used the computer code APX-Yield [Schmidt et al, 2014;Campbell et al, 2014;Berger et al, 2014], which employs GUAPX subroutines to calculate the yield of characteristic X-rays for elements from layered samples using fundamental PIXE and XRF principles. To do this, we used the computer code APX-Yield [Schmidt et al, 2014;Campbell et al, 2014;Berger et al, 2014], which employs GUAPX subroutines to calculate the yield of characteristic X-rays for elements from layered samples using fundamental PIXE and XRF principles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors presented abundances of the rock-forming elements, Al, Ca, Mg and Si (as well as Na) and provided a detailed description of analytical techniques, including the derivation of XRF line uxes and the conversion to elemental abundances. Berger et al 24 undertook experiments in their laboratory with the ight equivalent instrumentation to evaluate limitations in the analysis of thin particulate samples deposited on this tray and reported that apart from a drop in Fe and Mn signals, no signicant compositional differences were observed compared with surface measurements, except for a slight increase in Cl and S levels. Turning now to the Mars Science Laboratory Curiosity Rover, Campbell et al 23 reported changes to the basalt calibration target own on the mission and used to monitor the performance of the alpha particle excited XRF spectrometer.…”
Section: Hand-held Mobile On-line Xrf Techniques and Planetary Explmentioning
confidence: 99%